DETERMINANTS OF PROFITABILITY IN INDIAN BANKS: A PANEL DATA ANALYSIS - et. al., Sunaina Kuknor (International Journal of Modern Agriculture, 2021)
With every passing day, people come across scams and issues related to banks in India. People are perplexed that what determines a nice bank to rely their hard-earned money on. In pursuit of this, the current paper is an attempt to explore the determinants of profitability in banks. Data of 30 Indian commercial banks (including public and private sector banks) are taken for the last five years (FY 2014-15 to 2018-19). Static panel data econometrics is applied with a fixed effect. Profitability is regressed on regulation and NPA in banks. It is found that profitability in an Indian bank is positively related to regulation and negatively related to NPA in banks. The results were startling and significantly contribute to the existing lode of knowledge. The negative association of NPA with profitability is as expected but a positive association of regulation with profitability is a very surprising and encouraging result found in the study. The positive association of regulation with profitability has far-reaching implications for regulation in general and the profitability of banks in particular. These results can be a game-changer as regulation is often criticized to have a big dent in the profitability of the banks. However, the results of this paper support the ongoing debate that regulation has a positive impact on profitability. A study of the profitability of banks with more number of relevant variables and variables which are measured more effectively can be the future scope on the topic..